2022
DOI: 10.1029/2022tc007366
|View full text |Cite
|
Sign up to set email alerts
|

Refined Tectonic Evolution of the Betic‐Rif Orogen Through Integrated 3‐D Microstructural Analysis and Sm‐Nd Dating of Garnet Porphyroblasts

Abstract: The detailed deformation history of the Betic-Rif orogen (Figure 1) and its relationship with distinct metamorphic events recognized in this belt are still ambiguous as is reflected in disparate tectonic models that still differ on such fundamental aspects as the timing and polarity of subduction zones, the role of crustal extension versus compression, or the emplacement history of several peridotite massifs exposed in the belt (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 183 publications
2
5
0
Order By: Relevance
“…Li and Massonne (2018) identified Eocene monazite ages in the Mulhacén succession of the Sierra Nevada that support the Eocene 40 Ar/ 39 Ar data and suggest that the subduction of the NFC must have occurred prior to the Miocene metamorphic event. This was corroborated by Aerden et al (2022), who reported a late Eocene garnet Sm-Nd age (∼35 Ma).…”
Section: Eocene Metamorphismsupporting
confidence: 70%
See 4 more Smart Citations
“…Li and Massonne (2018) identified Eocene monazite ages in the Mulhacén succession of the Sierra Nevada that support the Eocene 40 Ar/ 39 Ar data and suggest that the subduction of the NFC must have occurred prior to the Miocene metamorphic event. This was corroborated by Aerden et al (2022), who reported a late Eocene garnet Sm-Nd age (∼35 Ma).…”
Section: Eocene Metamorphismsupporting
confidence: 70%
“…In this study, the new age constraints from the NFC indicate that Alpujárride and the NFC were subducted at similar times. Since Alpujárride is currently on the hanging wall of low‐angle normal faults, Alpujárride must have been subducted first, followed by the NFC in a lateral continuation of the same subduction system as recently described by several studies (Aerden et al., 2022; Porkoláb et al., 2022; Poulaki & Stockli, 2022). Previous models suggest that the subduction of the NFC occurs much later in the Miocene (e.g., Van Hinsbergen et al., 2020); however, our data, along with recently published data (Aerden et al., 2022; B. Li & Massonne, 2018; Porkoláb et al., 2022), suggests that the subduction of the NFC is likely to have commenced around the Early Eocene (Figure 9).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations